2009
DOI: 10.4149/neo_2009_05_455
|View full text |Cite
|
Sign up to set email alerts
|

Clonal evolution in chronic lymphocytic leukemia studied by interphase fluorescence in-situ hybridization

Abstract: The results of repeated interphase fluorescence in-situ hybridization (I-FISH, FISH) examination of 97 CLL patients and correlation of these findings with IgVH hypermutation status, ZAP-70 and CD38 expression are presented. The appearance of new, FISH-detectable, genomic aberrations during disease course, described as clonal evolution (CE), was observed in 26% of patients. The most frequent newly acquired cytogenetic abnormality was 13q deletion in 64% (16/25). In contrast to earlier studies, there was no corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 9 publications
2
29
1
Order By: Relevance
“…Other studies on clonal evolution in CLL have reported a correlation between unmutated IGHV genes, CD38 positivity and/or a high ZAP70 expression alone and clonal evolution, which corroborates the conclusion that patients with a more aggressively progressing disease are more likely to acquire new aberrations. 22,23,28,29 When evaluating the alterations that were acquired over time, we found that the del(13q) was the most common aberration in the follow-up samples, as 2/4 IGHV mutated and treated and 4/8 IGHV unmutated cases that underwent clonal evolution acquired this deletion. Thus, del(13q) is not only a common event in early stages of the disease, but can also develop during later stages when the disease progresses.…”
Section: R Gunnarsson Et Almentioning
confidence: 98%
See 1 more Smart Citation
“…Other studies on clonal evolution in CLL have reported a correlation between unmutated IGHV genes, CD38 positivity and/or a high ZAP70 expression alone and clonal evolution, which corroborates the conclusion that patients with a more aggressively progressing disease are more likely to acquire new aberrations. 22,23,28,29 When evaluating the alterations that were acquired over time, we found that the del(13q) was the most common aberration in the follow-up samples, as 2/4 IGHV mutated and treated and 4/8 IGHV unmutated cases that underwent clonal evolution acquired this deletion. Thus, del(13q) is not only a common event in early stages of the disease, but can also develop during later stages when the disease progresses.…”
Section: R Gunnarsson Et Almentioning
confidence: 98%
“…The follow-up studies have revealed clonal evolution in up to 43% of samples. [22][23][24][25][26][27][28][29] Besides the poor-prognostic deletion of 11q and 17p, deletion of 6q has also been implicated as a marker of recurrent progression. 2,23,29 Moreover, clonal evolution has been associated with unmutated IGHV genes, ZAP70 positivity, disease progression and poor outcome.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that biallelic del13q represents a more aggressive chromosomal abnormality than monoallelic deletion and is associated with an inferior progression free survival and a more frequent need of treatment [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the chromosomal abnormalities that were most frequently combined with other abnormalities were trisomy 12 and 13q deletion (55% and 35%, respectively), a finding comparable to the data published by Sindelarova et al [9] (46% and 38%, respectively). This suggests that CLL is a genetically unstable disease and clonal evolution is common in B-CLL patients [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, CE occurred more frequently among cases with unmutated IGVH status (Shanafelt et al, 2006;Stilgenbauer et al, 2007). However, another study did not find a correlation between CE and unmutated IGVH, expression of CD38 and ZAP70 on one hand, but the combination of all three prognostic factors correlated highly significantly with CE and with a shift from lower to higher FISH risk category (Berkova et al, 2009). Patients with CE showed progression to more advanced stages, greater need for therapy and a higher hazard ratio for death.…”
Section: Clonal Evolutionmentioning
confidence: 94%